INFLUENCE OF STATOR EMBRACE ON TORQUE OF IN-WHEEL SWITCHED RELUCTANCE MOTOR - Yıldırım, Merve; Kurum, Hasan (Hibetullah KILIÇ, 2017)
In this paper, influence of stator pole embrace on torque of In-Wheel Switched Reluctance Motor (IW-SRM) is investigated by numerical modeling based on Finite Element Method (FEM). For this reason, 3D numerical model of IW-SRM is built by using Ansys Maxwell Software Package. IW-SRM is analyzed and output torque and magnetic flux density of the IW-SRM are calculated. The analysis of IW-SRM is realized for different stator pole embraces and the results of the output torque and magnetic flux density of IW-SRM taken for various stator pole embraces are compared with each other. As seen from the results, when the value of stator pole embrace reduces, the output torque of IW-SRM increases. As a result in this study, the effects of different stator pole embraces are examined on the output torque of IW-SRM.
Keywords: Electrical Engineering; Elektrik Mühendisliği